2019
DOI: 10.1103/physrevb.99.165131
|View full text |Cite
|
Sign up to set email alerts
|

Many-body localization due to correlated disorder in Fock space

Abstract: In presence of strong enough disorder one dimensional systems of interacting spinless fermions at non-zero filling factor are known to be in a many body localized phase. When represented in 'Fock space', the Hamiltonian of such a system looks like that of a single 'particle' hopping on a Fock lattice in the presence of a random disordered potential. The coordination number of the Fock lattice increases linearly with the system size L in one dimension. Thus in the thermodynamic limit L → ∞, the disordered inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…We also add here that there is a tension between our predictions and the numerical results of Ref. [42], where it was reported that a many-body localised phase can exist only if the reduced covariance ρ r has a linear variation in r/N . However, the disordered transverse-field Ising model considered in this section provides a case in contrast to this claim; for the model is well known (on analytical grounds [22]) to host a many-body localised phase, yet has a covariance (Eq.…”
Section: Exact Diagonalisation Resultsmentioning
confidence: 53%
“…We also add here that there is a tension between our predictions and the numerical results of Ref. [42], where it was reported that a many-body localised phase can exist only if the reduced covariance ρ r has a linear variation in r/N . However, the disordered transverse-field Ising model considered in this section provides a case in contrast to this claim; for the model is well known (on analytical grounds [22]) to host a many-body localised phase, yet has a covariance (Eq.…”
Section: Exact Diagonalisation Resultsmentioning
confidence: 53%
“…Since the structure of this graph is rather involved it is normally approximated by either the Bethe lattice [33] or random-regular graphs (RRG, see also review by Imbrie et al [34]). In addition, the disorder residing on the nodes of this graph, is highly correlated, a feature which was shown to be important for MBL [35,36] compared to the Anderson problem on RRG. The first proposal of an intermediate nonergodic extended phase sandwiched between the deeply ergodic and insulating (MBL) phases appeared almost 20 years ago [33].…”
Section: Introductionmentioning
confidence: 99%
“…The second direction, arguably more microscopically motivated, has been to study the MBL problem as an unconventional Anderson localization problem [23] on the complex, correlated Fock-space graph of a quantum many-body system [5,18,19,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. While MBL on Fock space is inherently different from conventional Anderson localization on highdimensional graphs, the latter has served as an important inspiration for the former, with regard to both techniques and the scaling laws governing the transition [43][44][45][46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%